2019
DOI: 10.1017/s0967199419000157
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth it to cryopreserve embryos with blastulation delay at day 5?

Abstract: SummaryThis is a retrospective study over a 5-year period. In total, 3139 embryos were individually cryopreserved (Cryotop®) and warmed using the Kitazato vitrification/warming kit. They were classified into three categories based on their expansion degree. Transfer, implantation and pregnancy rates were assessed for each embryo category and compared using SPSS (Statistical Package for the Social Sciences) software. In total, 1139 couples enrolled in infertility treatment programme benefitted from embryo vitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Monjean et al showed that vitrifying slow kinetics embryos are a procedure worth envisaging as it generated a non-negligible chance of pregnancy in a five-year prospective study on individually cryopreserved (Cryotop ® ) and warmed (Kitazato vitrification/warming kit) embryos with endpoints of transfer, implantation, and pregnancy rates. The pregnancy versus transfer was as high as 30.3% in the grade-three embryos based on development [31].…”
Section: Embryo Cryopreservationmentioning
confidence: 96%
“…Monjean et al showed that vitrifying slow kinetics embryos are a procedure worth envisaging as it generated a non-negligible chance of pregnancy in a five-year prospective study on individually cryopreserved (Cryotop ® ) and warmed (Kitazato vitrification/warming kit) embryos with endpoints of transfer, implantation, and pregnancy rates. The pregnancy versus transfer was as high as 30.3% in the grade-three embryos based on development [31].…”
Section: Embryo Cryopreservationmentioning
confidence: 96%